Viscosity and density of isobutane measured in wide ranges of temperature and pressure including the near‐critical region. Issue 9 (2nd March 2015) - Herrmann, Sebastian; Hassel, Egon; Vogel, Eckhard
<x xml:space="preserve">Abstract</x> Accurate ηρpT data for isobutane were measured for nine isotherms between 298.15 and 498.15 K using simultaneously a vibrating‐wire viscometer and a single‐sinker densimeter. The maximum pressure was 93% of the saturated for subcritical isotherms and 30 MPa for supercritical isotherms. The density measurements are generally characterized by an uncertainty of ≤0.1%. Allocation errors for temperature and pressure influence significantly their uncertainty in the near‐critical region. A comparison with the equation of state by Bücker and Wagner shows agreement normally within ±0.1%. The near‐critical isotherm 410.15 K reveals differences to −3.7% exceeding the uncertainty of 1.9%. The uncertainty in viscosity is ≤0.3%. The comparison with the correlation of Vogel et al. yields deviations exceeding the uncertainty of the correlation (3%). The critical enhancement becomes evident for the near‐critical isotherm amounting to 1.4%. The new data will improve the viscosity surface correlation. © 2015 American Institute of Chemical Engineers AIChE J, 61: 3116–3137, 2015